STRATIGRAPHY AND FORMATION ENVIRONMENTS OF THE UPPER PERMIAN-TRIASSIC SEQUENCE IN THE AKSU-KENDYRLI FLEXURE AREA (SOUTHERN MANGYSHLAK) - Zhidovinov S.N.; Groshev V.G.; Volozh Yu.A.; Lipatova V.V. (My University, 1997)
Based on complex and voluminous geologic-geophysical data, relationships of pre-Jurassic sedimentary sections in the southern flank of the Southern Mangyshlak depression are outlined. Regional unconformities were established in the section, the main one of which (pre-late Olenekian) divides Upper Permian-Triassic deposits into two structural stages. It is shown that the Aksy-Kendyrli flexure comprises three carbonate members of different age (Early, Middle, and Late Triassic), every one of which is of interest for oil and gas prospecting. Description and correlation of local stratigraphic units are given and their formation environments are characterized.
Keywords: Triassic; Permian; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая; Палеозой::Пермская